A DESCRIPTIVE STUDY ON USING MULTIMEDIA LABORATORY TO THE STUDENTS’ ABILITY IN READING - Rahmawati Mamu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
English language as the first foreign language has been selected and accepted by our government to be taught, learned and used by the Indonesian generally. It also has been programmed in curriculum and must be taught start from elementary school up to the university. In English language there are two kinds of skill that must be taught to the student. The first is productive skills comprises speaking and writing and the second is receptive skills comprises listening and reading.